Laparoscopic resection of hepatocellular carcinoma: a French survey in 351 patients. Issue 4 (24th July 2013) - Soubrane, Olivier; Goumard, Claire; Laurent, Alexis; Tranchart, Hadrien; Truant, Stéphanie; Gayet, Brice; Salloum, Chadi; Luc, Guillaume; Dokmak, Safi; Piardi, Tullio; Cherqui, Daniel; Dagher, Ibrahim; et al.
Abstract Objectives Current clinical studies report the results of laparoscopic resection of hepatocellular carcinoma (HCC) obtained in small cohorts of patients. Because France was involved in the very early development of laparoscopic surgery, the present study was conducted in order to report the results of a large, multicentre experience. Methods A total of 351 patients underwent laparoscopic liver resection for HCC during the period from 1998 to 2010 in nine French tertiary centres. Patient characteristics, postoperative mortality and morbidity, and longterm survival were retrospectively reviewed. Results Overall, 85% of the study patients had underlying liver disease. Types of resection included wedge resection (41%), left lateral sectionectomy (27%), segmentectomy (24%), and major hepatectomy (11%). Median operative time was 180 min. Conversion to laparotomy occurred in 13% of surgeries and intraoperative blood transfusion was necessary in 5% of patients. The overall morbidity rate was 22%. The 30‐day postoperative mortality rate was 2%. Negative resection (R0) margins were achieved in 92% of patients. Rates of overall and progression‐free survival at 1, 3 and 5 years were 90.3%, 70.1% and 65.9%, and 85.2%, 55.9% and 40.4%, respectively. Conclusions This multicentre, large‐cohort study confirms that laparoscopic liver resection for HCC is a safe and efficient approach to treatment and can be proposed as a first‐line treatment in patients with resectable HCC.